Nanopesticides: From Research and Development to Mechanisms of Action and Sustainable Use in Agriculture - Fraceto, Leonardo F. [UNESP]; de Castro, Vera Lucia S. S.; Grillo, Renato [UNESP]; Ávila, Daiana; Oliveira, Halley Caixeta; Lima, Renata (Springer Nature, 2020)
This book explores the development of nanopesticides and tests of their biological activity against target organisms. It also covers the effects of nanopesticides in the aquatic and terrestrial environments, along with related subjects including fate, behaviour, mechanisms of action and toxicity. Moreover, the book discusses the potential risks of nanopesticides for non-target organisms, as well as regulatory issues and future perspectives.
Keywords: Agricultural nanosciences; ecotoxicology; Nanofungicides; Nanoherbicides; Nanoinsecticides; Nanomaterial; Nanotechnology; Pesticide techonology